Analisis Sentimen Ulasan Aplikasi PrimaKu Menggunakan Metode Support Vector Machine - Tinaliah Tinaliah; Triana Elizabeth (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The child's growth and development phase is very influential on the next phase. Where parents should be more careful in monitoring the growth and development of their children. Child development can be monitored with child growth and development applications, one of which is the PrimaKu application which can be accessed on the Google Play Store or App Store. Currently, the PrimaKu application has been downloaded 500 thousand times with a rating of 4.8. On the Google Play Store, you can see in the comments column regarding the reviews that have been filled in by PrimaKu application users. SVM is a method that gives better results in terms of classification, with the advantages of SVM being able to find the best hyperplane, separating one class from another class. In this study, sentiment analysis will be carried out on reviews of the PrimaKu application using the SVM method with a variety of kernels, namely linear kernel, polynomial kernel, and RBF Kernel. Based on the test results, it can be concluded that SVM can perform sentiment analysis on user reviews of the PrimaKu application well using a linear kernel with an accuracy value of 97.5% compared to using a polynomial kernel or RBF kernel.